A child brought up in foster family - Wosik-Kawala, Danuta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
This article is an attempt to show the complexity of the issues concerning the upbringingof a child in two families. Particular attention is paid to the difficult situation of the child, who periodically, by the court’s decision is sent to foster care and functions in a new unrelated family, while maintaining contact with their biological parents, with whom they share a legal bond. This situation raises a number of difficulties experienced by the child – dilemmas and problems with identification and belonging to the foster or biological family. The temporary nature of foster care, its subsidiary character, causes that nowadays the goal of foster families is not to establish ties with the child similar to those resulting from a parent-like attitude but to support, help in the care and upbringing of the child. The article also highlights the resulting threats to the proper functioning of the child.
Keywords: family; health; education; foster family; foster care; parental authority